2017
DOI: 10.1111/gfs.12308
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation during anthesis reduces seed set in perennial ryegrass

Abstract: In perennial ryegrass seed production, the establishment of seed yield potential occurs until the point of anthesis. However, utilizing potential seed yield is predominately focused on processes after anthesis, namely seed set (%) and seed filling. In practice, seed yield is the product of the number of harvested seeds remaining after cleaning and average seed weight. For this study, the anthesis patterns and seed set were recorded in a diploid variety grown in seed production fields in three different Danish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Irrigation was discontinued after flowering on the basis of previous research (Lambert 1967;Cookson et al 2000). In coolseason perennial grasses, many of the studies on irrigation (Lambert 1967;Hebblethwaite 1977;Chastain et al 2014) and precipitation during anthesis (Abel and Boelt 2018) suggested that wet weather and amount and timing of precipitation could depress pollination, as well reduce yield-component development. Nitrogen as granular ammonium nitrate (340 g N kg -1 ) was spread manually on the soil surface at the appropriate rates for the subplots receiving 25, 50 and 75 kg N ha -1 on 30 October 2009 (21 days after mowing for the first crop) and 25 February 2010 (20 days after mowing for the second crop).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…Irrigation was discontinued after flowering on the basis of previous research (Lambert 1967;Cookson et al 2000). In coolseason perennial grasses, many of the studies on irrigation (Lambert 1967;Hebblethwaite 1977;Chastain et al 2014) and precipitation during anthesis (Abel and Boelt 2018) suggested that wet weather and amount and timing of precipitation could depress pollination, as well reduce yield-component development. Nitrogen as granular ammonium nitrate (340 g N kg -1 ) was spread manually on the soil surface at the appropriate rates for the subplots receiving 25, 50 and 75 kg N ha -1 on 30 October 2009 (21 days after mowing for the first crop) and 25 February 2010 (20 days after mowing for the second crop).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…This ‘reproductiveCondition’ data was entered into the UBC database, following DarwinCore standards (Wieczorek, 2012). We focused on anthesis, as this is an identifiable phenological stage that occurs for a limited duration of time (Abel and Boelt, 2018)— Lolium perenne L. for example, is typically in anthesis for less than three weeks. Note that for simplicity, we refer to anthesis as flowering in the remainder of the manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…Arroyo, Chacon, and Cavieres (2006) found that changes in precipitation are closely related to seed longevity and directly reduce the seed density in the soil seed bank. Decreased precipitation affects the flowering period of plants, reducing their fruiting rate (Abel & Boelt, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Arroyo, Chacon, and Cavieres (2006) found that changes in precipitation are closely related to seed longevity and directly reduce the seed density in the soil seed bank. Decreased precipitation affects the flowering period of plants, reducing their fruiting rate (Abel & Boelt, 2017). In contrast, increased precipitation has been found to promote sexual reproduction in all species studied (Cleland et al., 2013) and increase the size of the seed bank through seed input.…”
Section: Introductionmentioning
confidence: 99%